Business statistics : communicating with numbers - Jaggia, Sanjiv , 1960-; Hawke, Alison Kelly (Business statistics, 2016)
"Overview: The first edition of Business Statistics: Communicating with Numbers provides a unique, innovative, and engaging learning experience for students studying Business Statistics. It is an intellectually stimulating, practical, and visually att